Prevalence and clinical significance of isolated low QRS voltages in young athletes . Issue 9 (4th March 2022) - Zorzi, Alessandro; Bettella, Natascia; Tatangelo, Mario; Del Monte, Alvise; Vessella, Teresina; Poscolieri, Barbara; Crescenzi, Cinzia; Pegorin, Davide; D'Ascenzi, Flavio; Pescatore, Valentina; Giada, Franco; Sarto, Patrizio; et al.
Abstract: Aims: Low QRS voltages (peak to peak <0.5 mV) in limb leads (LQRSV) on the athlete's electrocardiogram (ECG) may reflect an underlying cardiomyopathy, mostly arrhythmogenic cardiomyopathy (ACM) or non-ischaemic left ventricular scar (NILVS). We studied the prevalence and clinical meaning of isolated LQRSV in a large cohort of competitive athletes. Methods and results: The index group included 2229 Italian competitive athletes [median age 18 years (16–25), 67% males, 97% Caucasian] without major ECG abnormalities at pre-participation screening. Three control groups included Black athletes ( N = 1115), general population ( N = 1115), and patients with ACM or NILVS ( N = 58). Echocardiogram was performed in all athletes with isolated LQRSV and cardiac magnetic resonance (CMR) in those with ventricular arrhythmias or echocardiographic abnormalities. The isolated LQRSV pattern was found in 1.1% index athletes and was associated with increasing age (median age 28 vs. 18 years; P < 0.001), elite status (71% vs. 34%; P < 0.001), body surface area, and body mass index but not with sex, type of sport, and echocardiographic left ventricular mass. The prevalence of isolated LQRSV was 0.2% in Black athletes and 0.3% in young individuals from the general population. Cardiomyopathy patients had a significantly greater prevalence of isolated LQRSV (12%) than index athletes, Black athletes, and general population. Five index athletes with isolated LQSRV and exercise-induced ventricular arrhythmias underwent CMR showing biventricular ACM in 1 and idiopathic NILVS in 1. Conclusions: Unlike cardiomyopathy patients, the ECG pattern of isolated LQRSV was rarely observed in athletes. This ECG sign should prompt clinical work-up for exclusion of an underlying cardiomyopathy. Graphical Abstract: